Spectroscopic Investigation of Protein Binding and Antibacterial Activity in Hybrid CuO–Bi(III) Schiff Base Complexes - pandian, S. Rama; Mathavan, A.; Vedhi, C. (Journal of Neonatal Surgery, 2025)
This study presents the development and characterization of hybrid CuO–Bi(III) Schiff base nanocomposites. Copper oxide nanoparticles were synthesized via a simple precipitation method and functionalized with a salen ligand and a bismuth-salen complex, forming CuO–Salen and CuO–SBC. Spectroscopic analyses (FT-IR, UV-Vis) confirmed successful coordination, with characteristic Cu–O bands and LMCT absorption up to 700 nm. The optical band gap reduced from 2.27 eV (CuO) to 1.99 eV (CuO–SBC), indicating enhanced charge transfer. FE-SEM showed a porous structure, and XRD confirmed nanoscale crystallinity. Binding studies with BSA and HSA revealed strong interactions, especially for CuO–SBC (Ka: 1.2 × 10⁵ M⁻¹ and 3.5 × 10⁵ M⁻¹). Antibacterial tests showed CuO–SBC had the highest activity, with a 19 mm inhibition zone against Bacillus subtilis. Overall, CuO–SBC demonstrated excellent biological activity, highlighting its potential in drug delivery and antimicrobial applications.